Glycosyltransferase Family 61 in Liliopsida (Monocot): The Story of a Gene Family Expansion - Cenci, Alberto; Chantret, Nathalie; Rouard, Mathieu (Frontiers in Plant Science, 2018)
Plant cell walls play a fundamental role in several plant traits and also influence crop use as livestock nutrition or biofuel production. The Glycosyltransferase family 61 (GT61) is involved in the synthesis of cell wall xylans. In grasses (Poaceae), a copy number expansion was reported for the GT61 family, which raised the question of the evolutionary history of this gene family. A phylogenetic study was performed on GT61 members from 13 species representing the major angiosperm clades to classify the genes, reconstruct the evolutionary history of this family and study its expansion in monocots. Five orthogroups were defined in angiosperms, only two of which show a copy number expansion in monocots. These copy number expansions result from both tandem and segmental duplications during the genome evolution of monocot lineages. We suggest that the gene number expansion of GT61 was accompanied by functional diversification and propose a classification of the angiosperm GT61 genes based on orthogroups defined at different taxonomic levels.